Democratic education and indigenous knowledge systems in South African schools: convergence or divergence - Sonkqayi, Gift Siphosethu (My University, 2020)
The denotation of the word ‘democracy’ remains widely disputed. Undoubtedly, democracy has sometimes been conceived as a system of governance whereby citizens have political power and can influence decisions either directly (i.e. direct participation) or indirectly (i.e. representation). The notion of what should constitute a democratic society has been a subject of contestation for decades. Nonetheless, many of the debates on the subject of democracy have been concerned with the nature in which such power should be vested in the hands of the people. It is evident in almost all different conceptions of democracy that a citizen is thought to be an ‘autonomous being’. It is in light of this view that democratic education seeks to cultivate ‘conscious social reproduction’ in order to produce independent citizens who ought to shape and sustain democratic societies. In this thesis, I investigate the nature of the knowledge necessary to cultivate an ‘autonomous being’. Moreover, I explore the debates on the nature of indigenous knowledge systems to find out if such notions of multiple factually ‘true’ knowledge systems converge with the knowledge required to cultivate ‘conscious social reproduction’ as envisaged by Gutmann’s theory of democratic education. In so doing, I use epistemological realism as a meta-theoretical framework in order to establish the meaning and nature of that which is considered ‘factual or propositional’ knowledge. In this study, I further examine specific examples of indigenous knowledge systems in three of the post-apartheid curriculum statements; namely, the Revised National Curriculum Statements (RNCS), National Curriculum Statements (NCS) and Curriculum Assessment Policy Statements (CAPS). As a point of exit, I propose a new realist rejoinder which is a meta-evaluative framework or criteria which advocates for the inclusion or teaching of a universally true factual knowledge that is rooted in ‘true identities’ of indigenous people or societies
A report submitted n fulfilment of the requirements of the degree of Master of Education by research to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020
Keywords: Democracy and education; Democracy--Study and teaching